COMPUTED TOMOGRAPHY MESIADISTAL SIZE OF TEETH IN BOYS WITH PHYSIOLOGICAL BITE DEPENDING ON THE FORM OF HEAD - Марченко, А.В. (World of Medicine and Biology, 2015)
Aim of our work – determine the features of computer-tomographic mesiadistal size of teeth in young men with physiological bite, depending on the shape of the head. Materials and methods The primary indicator of the size of the teeth and head boys of Podillya with orthognathic bite derived from the database of SRC VNMU named after Pirogov. To study were selected only scans of boys with orthognathic bite, which was determined by 11-points by Bushan et al. and their cephalometry performance. To conduct computer tomographic studies used dental cone-beam tomograph - Veraviewepocs 3D, Morita (Japan). Research conducted under the own developed schemes within the following specifications. Volume three-dimensional image - cylinder 8х8sm, – the layer thickness 0,2/0,125 mm, dose of radiation 11-48 mkSv, voltage and amperage 60-90kV/2-10mA. Measuring the mesiadistal size of teeth conducted exploring tomograms in shell program i-Dixel One Volume Viewer [Ver.1.5.0] J Morita Mfg. Cor. Measurements were carried out according to the following protocol: 1) adjusted the brightness and contrast of the image so as to clearly distinguish the skeletal anatomy; 2) study tooth positioned so that its central axis coincide with the vertical, horizontal and sagittal axes of the program. As a result, we received the presentation of the object studied in three windows. Mesiadistal size measurement performed using regular software measuring device in the corresponding projection. In the upper incisors, canines, small and first large molar teeth measured mesiadistal distance between the most distant (contact) points of approximal surfaces in the lower incisors - at a level the cutting edge. Cephalometry size measurement is carried out within the program measurements corresponding list of Martin. Head linear dimensions defined as direct or projection distance between anthropometric points. The measurements were performed a large compass with scale full-scale systems of Martin. To determine craniotipe defined the parameters largest width of the head and longest length head. Craniotipe determined by the formula: the largest head width * 100 / greatest length head. With the value to the 75.9 researched attributed to dolichocephalic; 76,0-80,9 - to mesocephalic; 81,0-85,4 - to brachycephalic. Established the following distribution: mesocephalic boys - 16, boys brachycephalic - 19 Statistical analysis of the results was performed using the statistical software package "Statistica 6,0" (belongs to Vinnitsa National Medical University named after Pirogov, license number AXXR910A374605FA) using nonparametric methods. Results. Discussions Established that only size mesiadistal size of the lower right canine in males brachycephalic significantly (